Explaining differential effects of medication for opioid use disorder using a novel approach incorporating mediating variables. (22nd January 2021) - Rudolph, Kara E.; Díaz, Iván; Hejazi, Nima S.; van der Laan, Mark J.; Luo, Sean X.; Shulman, Matisyahu; Campbell, Aimee; Rotrosen, John; Nunes, Edward V.
Abstract: Background and Aims: A recent study found that homeless individuals with opioid use disorder (OUD) had a lower risk of relapse on extended‐release naltrexone (XR‐NTX) versus buprenorphine–naloxone (BUP‐NX), whereas non‐homeless individuals had a lower risk of relapse on BUP‐NX. This secondary study examined differences in mediation pathways to medication effect between homeless and non‐homeless participants. Design: Secondary analysis of an open‐label randomized controlled, 24‐week comparative effectiveness trial, 2014–17. Setting: Eight community addiction treatment programs in the United States. Participants: English‐speaking adults with DSM‐5 OUD, recruited during inpatient admission ( n  = 570). Intervention(s): Randomization to monthly injection of XR‐NTX or daily sublingual BUP‐NX. Measurements(s): Mediation analysis estimated the direct effect of XR‐NTX versus BUP‐NX on relapse and indirect effect through mediators of medication adherence, use of illicit opioids, depressive symptoms and pain, separately by homeless status. Findings: For the homeless subgroup, the protective indirect path contributed a 3.4 percentage point reduced risk of relapse [95% confidence interval (CI) = −12.0, 5.3] comparing XR‐NTX to BUP‐NX (explaining 21% of the total effect). For the non‐homeless subgroup, the indirect path contributed a 9.4 percentage point increased risk of relapse (95% CI = 3.1, 15.7) comparing XR‐NTX to BUP‐NX (explaining 57% of the total effect). Conclusions: A novel approach to mediation analysis shows that much of the difference in medication effectiveness (extended‐release naltrexone versus buprenorphine–naloxone) on opioid relapse among non‐homeless adults with opioid use disorder appears to be explained by mediators of adherence, illicit opioid use, depressive symptoms and pain.